2019
DOI: 10.1016/j.pec.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Patient centred consultation, satisfaction and young patients: A cross-country analysis

Abstract: Objectives: The aim of this study was to investigate the link between perceived dimensions of patient centred care and the satisfaction of adolescents and young adults within the UK, USA, Australian, Italian, and Chinese healthcare systems. Methods: One thousand and thirty-four participants (212 from China,206 from Australia,208 from UK, 202 from USA, and 206 from Italy) answered a self-report questionnaire assessing the perceived dimensions of patient centred care. Factor analysis (PFA) was conducted on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Khomami [36] found a positive relationship between patient satisfaction and their willingness to cooperate with nurses. Conti and Humphris [37] indicated that patient satisfaction has a positive effect on the duration of the relationship between patients and physicians. According to prior studies, satisfaction may be a factor affecting patients’ willingness to cooperate with clinical pharmacists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khomami [36] found a positive relationship between patient satisfaction and their willingness to cooperate with nurses. Conti and Humphris [37] indicated that patient satisfaction has a positive effect on the duration of the relationship between patients and physicians. According to prior studies, satisfaction may be a factor affecting patients’ willingness to cooperate with clinical pharmacists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Good communication, understanding, and empathy should be practiced in all dental care, not just to treat patients with special needs (Kulich et al, 2003). Communication is essential in treating young patients (Conti & Humphris, 2019) Treatment-and personnel-related factors were associated with dental care situations when placed on a timeline here. This is of utmost importance in fear-arousing situations like during surgical operations and extractions and patients should be given ways to cope with those situations.…”
Section: Discussionmentioning
confidence: 99%
“…Good communication, understanding, and empathy should be practiced in all dental care, not just to treat patients with special needs (Kulich et al, 2003 ). Communication is essential in treating young patients (Conti & Humphris, 2019 ). Most of the suggestions for improvements included some examples or aspects of two‐way dialog: “I like when the dentist tells what he/she is doing and asks me often if I am fine” (female, 36 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations